PENGGUNAAN MEDIA PREZI DESKTOP FOREVER UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATERI LAJU REAKSI KELAS XI DI SMA NEGERI 1 SUNGAI APIT - Dora Ariska Ariska; Susilawati '; Rini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research was conducted in Senior High School 1 Sungai Apit. This research aims to increase student achievement on the subject of reaction rate in class XI Senior High School 1 Sungai Apit.  This research is a kind of experiment research with pretest-posttest design. The sample consists of two classes which were decided randomly after doing normality and homogenity test. Experimental class is a class that is used media Prezi Desktop  Forever, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tcount> ttable is 1,78 > 1,67, means that the Prezi Desktop Forever can improve student achievement on the subject of reaction rate in class XI Senior High School 1 Sungai Apit where the effect of an increase is 5,435%. Keywords: Prezi  Desktop Forever, Learning Achievement, and Reaction Rate